Diazonium Salts as Grafting Agents and Efficient Radical‐Hydrosilylation Initiators for Freestanding Photoluminescent Silicon Nanocrystals. Issue 15 (24th March 2014) - Höhlein, Ignaz M. D.; Kehrle, Julian; Helbich, Tobias; Yang, Zhenyu; Veinot, Jonathan G. C.; Rieger, Bernhard
Abstract The reactivity of diazonium salts towards freestanding, photoluminescent silicon nanocrystals (SiNCs) is reported. It was found that SiNCs can be functionalized with aryl groups by direct reductive grafting of the diazonium salts. Furthermore, diazonium salts are efficient radical initiators for SiNC hydrosilylation. For this purpose, novel electron‐deficient diazonium salts, highly soluble in nonpolar solvents were synthesized. The SiNCs were functionalized with a variety of alkenes and alkynes at room temperature with short reaction times.